Giovanni Frau, Dizionario toponomastico del Friuli-Venezia Giulia. Udine, Istituto per L'Enciclopedia del Friuli-Venezia Giulia, 1978. Pp. 130. - Eric P. Hamp (Linguistica, 1988)
This first integral collection of the place names of this complex and interesting region is avowedly intended as a work for general interest - as such it does not claim to be exhaustive and has not been delayed until all Flurnamen could be collec ted; but in fact Frau has given us a thoroughly scholarly work. A highly informative introduction (5-24), adorned with seven reproductions of older maps and plans, is followed by the dictionary proper. The front matter includes maps (showing comu ni) of the four provincie of the region, an excellent concise bibliography of 26 items, a useful brief glossary of technical terms, and some welcome remarks on the contri bution of toponomastics as a discipline.